Undertaking a scoping review: A practical guide for nursing and midwifery students, clinicians, researchers, and academics - Pollock, Danielle; Davies, Ellen L.; Peters, Micah D. J.; Tricco, Andrea C.; Alexander, Lyndsay; McInerney, Patricia; Godfrey, Christina M.; Khalil, Hanan; Munn, Zachary (Journal of advanced nursing, 2021)
Aim The aim of this study is to discuss the available methodological resources and best‐practice guidelines for the development and completion of scoping reviews relevant to nursing and midwifery policy, practice, and research. Design Discussion Paper. Data Sources Scoping reviews that exemplify best practice are explored with reference to the recently updated JBI scoping review guide (2020) and the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses Scoping Review extension (PRISMA‐ScR). Implications for nursing and midwifery Scoping reviews are an increasingly common form of evidence synthesis. They are used to address broad research questions and to map evidence from a variety of sources. Scoping reviews are a useful form of evidence synthesis for those in nursing and midwifery and present opportunities for researchers to review a broad array of evidence and resources. However, scoping reviews still need to be conducted with rigour and transparency. Conclusion This study provides guidance and advice for researchers and clinicians who are preparing to undertake an evidence synthesis and are considering a scoping review methodology in the field of nursing and midwifery. Impact With the increasing popularity of scoping reviews, criticism of the rigour, transparency, and appropriateness of the methodology have been raised across multiple academic and clinical disciplines, including nursing and midwifery. This discussion paper provides a unique contribution by discussing each component of a scoping review, including: developing research questions and objectives; protocol development; developing eligibility criteria and the planned search approach; searching and selecting the evidence; extracting and analysing evidence; presenting results; and summarizing the evidence specifically for the fields of nursing and midwifery. Considerations for when to select this methodology and how to prepare a review for publication are also discussed. This approach is applied to the disciplines of nursing and midwifery to assist nursing and/or midwifery students, clinicians, researchers, and academics. 摘要 目的 本研究旨在讨论可用的方法论资源和最佳实践指南, 以便确定和执行涉及护理和助产政策、实践及研究的范围审查。 设计 讨论稿。 数据来源 参考最近更新的JBI范围审查指南 (2020年) 以及系统审查和荟萃分析范围审查扩展的首选报告项目 (PRISMA‐ScR) , 以便探讨最佳实践的范围审查程序。 护理和助产学启示 范围审查可用于合成证据, 目前越来越普遍。其主要用于解决大量研究问题, 并汇集通过不同来源获得的证据。范围审查是一种有用的证据合成方式, 适用于护理和助产程序, 并可为研究人员提供机会, 帮助其审查广泛的证据和资源。然而, 仍应严格执行范围审查程序, 且应保证其透明度。 结论 本研究可为研究人员、临床医师提供指导和建议, 帮助其合成证据, 并在护理和助产领域应用范围审查方法。 影响 伴随着范围审查日益普及, 多个学术和临床学科人员提出应保证方法的严谨性、透明度和适当性, 包括护理和助产学。本讨论稿的重点在于范围审查的各组成部分, 包括: 提出研究问题和目标; 制定方案; 确定资格标准和拟议搜索方法; 寻找和选择证据; 提取和分析证据; 展示结果以及概述护理和助产领域的具体证据。此外, 讨论内容包括方法选择时间和评论发表方法。此方法适用于护理和助产学科, 可用于协助护理和/或助产学生、临床医生、研究人员和学术人员。